LIFE CYCLE ENVIRONMENTAL ANALYSIS OF BRICK PRODUCTION: TURKEY AS A CASE STUDY - Oztas, Saniye Karaman; Yuksek, Izzet (College Publishing, 2022)
Brick production has significant environmental impacts; its use of coal in particular emits CO2 emissions and pollutants. Despite the Turkish brick industry's use of coal in its firing process, there is no environmental data for its fired brick production. This study thus aims to obtain local environmental data, assess environmental impacts, and contribute to product and process development for sustainable fired brick in Turkey. For this purpose, two Turkish brick factories of different kiln types, Hoffman and tunnel, were monitored for environmental sustainability as case studies. A Life Cycle Assessment (LCA) was used in the system boundary from cradle-to-gate. After the acquisition of the factories inventory data, their environmental impacts were assessed and compared. The study then uses these results to determine the life cycle phases most important in supporting decision-making by designers and practitioners and the contribution of each phase to the total environmental burden for each impact category. It was determined that manufacturing is the most relevant life cycle phase for all impact categories except terrestrial ecotoxicity and water consumption. The Hoffman factory gives more favorable results than the tunnel factory for all impact categories, with the exceptions of fine particulate matter formation and mineral resource scarcity. These results may allow for comparison with other studies on the environmental impacts of fired brick production.
Keywords: brick; cleaner production; cradle-to-gate; LCA; kiln type